Amniotic Fluid and Maternal Serum Laeverin Levels and Their Correlations with Fetal Size and Placental Volume in Second Trimester of Pregnancy—A Prospective Cross-Sectional Study - János Sikovanyecz; Giuseppe Gullo; Márió Vincze; Imre Földesi; Gábor Németh; Andrea Surányi; János Sikovanyecz; Zoltan Kozinszky (Diagnostics)
Background: Laeverin is an extravillous trophoblast marker playing a significant role in trophoblast migration. We endeavored to estimate the association between the amniotic and serum laeverin concentrations at 16–22 weeks of gestation and the fetal and placental ultrasound measurements in high-risk uncomplicated pregnancies. Methods: A prospective cross-sectional study of consecutively recruited singleton pregnancies undergoing amniocentesis was performed. Fetal structural malformations and/or aneuploidy were the exclusion criteria. Fetal biometric parameters and placental growth/perfusion were assessed by ultrasound in 44 high-risk pregnancies who had no pregnancy complications and any other chronic disease. Maternal serum and amniotic laeverin levels were essayed with sandwich enzyme-linked immunosorbent assay. Results: Serum laeverin levels are decreasing marginally with the maternal age in mid-gestation. Laeverin levels in the serum correlated minimally negatively with head size of the fetus (β = −0.38; p < 0.05; 95% confidence interval (CI) −0.03–0.01), whereas the amniotic level correlated strongly with the fetal abdominal circumference (β = −0.74; p < 0.05; 95% CI: −0.34–−0.09). In addition, the amniotic laeverin level correlated moderately and positively with the placental volume (β = 0.46; p < 0.05; 95% CI: 0.01–0.08). Conclusions: Laeverin levels detected in the serum and in the amniotic fluid denote the fetoplacental growth in uncomplicated high-risk pregnancies.